Study on clinical profile, electrolyte and electrocardiographic abnormalities in patients with yellow oleander poisoning - D.K., Sivakumar; G., Nithya (International Journal of Advances in Medicine, 2018)
ABSTRACT Background: Poisoning occurs following the ingestion of crushed seeds or fruits of yellow oleander. Objectives of the study were to investigate various arrhythmias and electrolyte abnormalities seen in patients with yellow oleander poisoning and to find out the correlation between various arrhythmias, duration and form of exposure of oleander. Methods: Fifty patients from the toxicology ward in the Institute of Internal Medicine, Madras Medical College and Rajiv Gandhi Government General Hospital, Chennai, who fulfilled the eligibility criteria, were enrolled for this prospective and observational study among the patients admitted for the ingestion of yellow oleander. Results: Oleander seed poison was most prevalent in the 21-40 years of age. Incidence was more among the young males. Mortality was independent of the number of seeds consumed. More the crushed seeds consumed and delay to admission to the hospital, poorer was the outcome. ECG abnormalities were found in majority of the individuals. Electrolyte disturbances (hyperkalemia and hypermagnesemia) were found in significant proportion of the patients. Conclusions: Prognosis was poor among those who presented with bradycardia, electrolyte disturbances and complex arrhythmias. The arrhythmias produced by this poisoning might range from sinus bradycardia to complete heart block and ventricular tachycardia. Sinus bradycardia was the most common arrhythmia seen in this study. As there are no standard guidelines at present to recommend the indications for temporary pacemaker in the management of oleander induced arrhythmias, uniform guidelines have to be formulated.